The Transformation of Zakat From a Religious Obligation to a Socio-Economic Empowerment Mechanism - Nuraini, Nabilah; Syauqi Aulade Ghifari (Westscience Press, 2025)
Zakat is a key Islamic institution designed to promote social welfare, as mandated in the Qur’an and Sunnah. However, in contemporary practice, zakat has not yet effectively addressed economic disparities within the Muslim community. Fazlur Rahman, a leading modern Islamic scholar, reinterprets zakat using the Double Movement method, aligning its objectives with present socio-economic realities and advocating its integration into fiscal policies, including its potential role as an Islamic tax system. Through library research on Rahman’s works and secondary sources, this study finds that zakat is fundamentally a divine mandate aimed at transforming mustahik (recipients) into muzakki (givers) through productive means, fostering economic self-sufficiency. Rahman views zakat as evolving from a purely spiritual obligation into a mechanism of social empowerment, historically administered from the time of Prophet Muhammad SAW to today as a tool for economic redistribution and justice. The study highlights the ideal moral implications of zakat in enhancing productivity and social welfare. Key aspects include effective zakat management, equitable distribution, timing, and measurement, which can be adapted to modern economic conditions. By implementing these principles, zakat can function as a sustainable instrument for economic empowerment, ensuring both spiritual and material prosperity within the Muslim community